2005
DOI: 10.1007/s10029-005-0009-7
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin sealing versus stapling of hernia meshes in an onlay model in the rat

Abstract: Incisional and inguinal hernia repair are among the most common procedures of general surgery. Mesh fixation by means of staples or sutures may lead to severe complications. The use of fibrin sealant (FS) has been suggested as alternative, but data on biocompatibility and adhesive strength of FS in combination with macroporous meshes is limited. Ventral hernia (n = 8 per group) was treated in rats in onlay technique with two types of meshes, fibrin sealed or stapled. TI-Mesh (TMxl) extralight and VYPROII (VPII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 21 publications
6
68
0
Order By: Relevance
“…[19][20][21] Our results support those reported by other authors 22 in that no collagen-derived material has shown intrinsic antimicrobial activity. Neither were we able to observe inhibition halos around the biomeshes when cultured in the presence of Sa and Se.…”
Section: Discussionsupporting
confidence: 95%
“…[19][20][21] Our results support those reported by other authors 22 in that no collagen-derived material has shown intrinsic antimicrobial activity. Neither were we able to observe inhibition halos around the biomeshes when cultured in the presence of Sa and Se.…”
Section: Discussionsupporting
confidence: 95%
“…Mesh fixation with fibrin glue is a quick and reliable method, as borne out not only by the biomechanical results of our tests [35,36]. While it was not possible to obtain essentially higher tensile strength values for suture reinforcement with fibrin glue alone, the specified retention force value was significantly exceeded through the additional use of a mesh.…”
Section: Discussionmentioning
confidence: 91%
“…But, once again, the question arises as to how such meshes are to be fixed so that they can assume an effective prophylactic role. By means of other models of hernia repair, it was possible to demonstrate that mesh fixation with fibrin glue could be equated with sutureor staples-based fixation [35][36][37] and that this could even expedite mesh integration into the surrounding tissue.…”
Section: Introductionmentioning
confidence: 98%
“…However, it is the first time such a study has been done, and it could be useful if extrapolation to humans proves possible. We will also have to study the influence of the size of the meshes, their structure, the materials used, and the use of biological glues to enhance resistance [15,16].…”
Section: Discussionmentioning
confidence: 99%